RANKL neutralisation prevents osteoclast activation in a human in vitro ameloblastoma-bone model. (December 2022) - Pape, Judith; Bakkalci, Deniz; Hosni, Rawiya Al; Simpson, Benjamin S; Heikinheimo, Kristiina; Fedele, Stefano; Cheema, Umber
Ameloblastoma is a benign, locally invasive epithelial odontogenic neoplasm of the jaw. Treatment of choice is jaw resection, often resulting in significant morbidity. The aim of this study was to recapitulate ameloblastoma in a completely humanised 3D disease model containing ameloblastoma cells, osteoblasts and activated osteoclasts to investigate the RANKL pathway within the ameloblastoma stromal environment and its response to the RANKL antibody denosumab. In vitro bone was engineered by culturing human osteoblasts (hOB) in a biomimetic, dense collagen type I matrix, resulting in extensive mineral deposits by day 21 forming alizarin red positive bone like nodules throughout the 3D model. Activated TRAP + human osteoclasts were confirmed through the differentiation of human CD14+ monocytes after 10 days within the model. Lastly, the ameloblastoma cell lines AM-1 and AM-3 were incorporated into the 3D model. RANKL release was validated through TACE/ADAM17 activation chemically or through hOB co-culture. Denosumab treatment resulted in decreased osteoclast activation in the presence of hOB and ameloblastoma cells. These findings stress the importance of accurately modelling tumour and stromal populations as a preclinical testing platform.